EFFECT OF Nd-YAG LASER HYALOIDOTOMY FOR PRE-MACULAR HEMORRHAGE IN TERMS OF SUCCESS AND VISUAL OUTCOME - Khan, Sher Akbar; Aftab, Muhammad; Sethi, Junaid; Alam, Mumtaz; Alam, Adnan; Hussain, Mahfooz (Journal of Postgraduate Medical Institute, 2019)
Objective: To find out the effect of Nd-YAG laser hyaloidotomy for pre-macular hemorrhage in terms of success and visual outcome. Methodology: This case series study was performed at Saidu Teaching Hospital, Swat and Lady Reading Hospital, Peshawar, from January 2016 to December 2017. Patients with pre-macular hemorrhage of any etiology who could sit comfortably on slit lamp were included in the study. Nd YAG laser posterior hyaloidotomy was performed. Patients with creation of an opening and bleeding into vitreous cavity after applying laser were termed successful. Follow-up was done at 1, 3 and 6 weeks intervals. On each visit, visual acuity was checked. Data were entered into SPSS version 20 and analyzed for descriptive statistics. Results: Total 37 patients were included in this study. The most common causes of pre-macular hemorrhage were proliferative diabetic retinopathy in 20 (54.05%) cases, ocular trauma in 6 (16.21%) cases and valsalva retinopathy in 5 (13.51%) cases. The procedure was successful in 33 (89.18%) patients; however 2 of them had persistent vitreous hemorrhage. After laser treatment, visual acuity improved in 32 (86.48%) patients. No complications of the procedure were seen in any of the patient. Conclusion: Nd-YAG laser hyaloidotomy was found to be effective procedure as it was successful with improved visual acuity in most of the patients.